Design to Build an Arduino-Based Heart Rate Detection Device - M. Ariq Zhilal Manafi; Muhammad Ihsan (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2026)
The development of technology in the modern era is currently taking place very rapidly and has had a significant impact on various aspects of human life, one of which is in the health sector. Advances in electronics technology and embedded systems have allowed the creation of various health devices that are portable, practical, and easy to use by the wider community. In the health sector, monitoring the condition of the human body is very important, especially in knowing a person's vital condition. One of the vital parameters that is often used as an indicator of health is heart rate. However, in reality, heart rate detection devices available on the market generally have relatively expensive prices and not all people have access to these tools. The researcher designed an Arduino Uno-based heart rate detection device that is simple, economical, and easy to use This research designed a biometric system that measures heart rate and body temperature while based on Arduino Uno and heart rate sensors. The system is designed to be low cost, easy to use, and can be upgraded again in the future.